Improving Mobile Core Network Security with Honeynets. - Dimitriadis, C.K.
Despite improved security, core network vulnerabilities continue to threaten third-generation (3G) mobile systems. This article offers a security assessment conducted in the packet-switched domain of a mobile operator's infrastructure. A honeynet architecture could help address 3G security.
Keywords: Honeynet architecture; Mobile core network security; Mobile operator infrastructure; Packet-switched domain; Third-generation mobile system